TERRITORIAL PECULIARITIES OF THE LEGISLATION OF THE SYSTEM OF ADAPTATION AND INTEGRATION OF MIGRANTS IN THE NORTH CAUCASUS - I. A. Soloviev; V. S. Belozerov (Наука. Инновации. Технологии, 2022)
Introduction. The article. Based on research materials and analysis of legislative and regulatory acts, revealed the spatial and temporal features of state and regional policies on the adaptation and integration of migrants in the North Caucasus. A key element of the research is a systematic approach to the consideration of the territorial features of the state and regional adaptation and integration policies in the North Caucasus. Materials and methods. The main research tools were analytical, historical reconstruction, comparative geographical and comparative historical methods. Discussion of the research results. The article discusses the transformations of the territorial features of the system of adaptation and integration of migrants in the North Caucasus for more than two centuries. The authors propose a geographically three-tier adaptation system (levels: country, regional, local) and migrant integration in the state and regional migration policies in the North Caucasus, consisting of a set of legislatively established measures (measures: ethnocultural, legal, social, economic). Findings. In the pre-reform period, a system of mechanisms and measures for the adaptation and integration of migrants took place, which subsequently underwent certain changes depending on the political course of the state, the socio-economic needs of the North Caucasus regions and the change of socio-economic formations.